(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2026)
Background and Design: Type 1 diabetes mellitus (T1DM) can cause significant changes in the skin. However, there are limited studies examining skin findings in children with T1DM. This study aims to determine the frequency of skin lesions in children with T1DM and evaluate their relationship with disease duration and hemoglobin A1c (HbA1c) levels. Materials and Methods: the study was including 49 children with diabetes mellitus type 1 and 60 age- and sex-matched healthy children. The children were examined in detail by a pediatrician and dermatologist . Results: Children’s age at beginning of the diabetes was 7.0 ± 3.5 years, and duration of illness was 49.8 ± 38.7 months. The average of HbA1c was 8.2 ± 1.7%. Out of the total of 49 subjects in the study, 9 (18.4%) used an insulin pump, and 40 (81.6%) used multiple daily injections of insulin. In 41 patients (83.7%) at least one associated skin condition caused by insulin. The most common adverse effects were lipohypertrophy, ecchymosis and post-inflammatory hyperpigmentation. Patients with diabetes type 1 were more likely to have occurrences of xerosis and rubeosis faciei compared to controls which were statistically significant 28.6%vs. 10.0% and 10.2%versus 1.7% respectively. Facial erythema patients showed higher body mass index (BMI) levels.. Conclusion: Training patients and caregivers and increasing physician awareness can improve management and prevention of skin findings in children with T1DM.